1986
DOI: 10.1111/j.1095-8649.1986.tb04976.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria—food or food competitors of silver carp, Hypophthalmichthys molitrix Val.?

Abstract: The role of bacteria in the nutrition of silver carp was studied by in-vim tests, which confirmed earlicr results that the potentially important source of nitrogen in bacteria is not utilized by the fish. Cultures of aerobic and anaerobic bacteria, recovered from a fish pond, were incubated with digestive fluids from the gut contents and from tissues surrounding the alimentary tract (Organ of Leydig) respectively. Growth of aerobic isolates was not affected by the digestive fluids whereas growth of all anaerob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
2

Year Published

1991
1991
2003
2003

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 13 publications
1
1
0
2
Order By: Relevance
“…In the early larval stages of marine fish, endocytosis might provide a supply of essential factors not degradable in the gut lumen. This supports the contention that ingested bacteria may have a nutritional or otherwise stimulating effect (3,25,41). Given the abundance of bacteria, the morphology of the gut, and the observed endocytosis by hindgut enterocytes of herring larvae (32), it appears that the gut microflora could play an important part for this fish species by producing essential nutrients, e.g., fatty acids or vitamins, or exposing antigenic determinants.…”
Section: Discussionsupporting
confidence: 57%
“…In the early larval stages of marine fish, endocytosis might provide a supply of essential factors not degradable in the gut lumen. This supports the contention that ingested bacteria may have a nutritional or otherwise stimulating effect (3,25,41). Given the abundance of bacteria, the morphology of the gut, and the observed endocytosis by hindgut enterocytes of herring larvae (32), it appears that the gut microflora could play an important part for this fish species by producing essential nutrients, e.g., fatty acids or vitamins, or exposing antigenic determinants.…”
Section: Discussionsupporting
confidence: 57%
“…12. Columnar epithelial cells in the hindgut of a 5-day-old larva exposed to Vibrio salmonicida for 72 h. enzymes, induce enzyme release before first feeding, or provoke early immune development (Lindsay & Godday, 1985;Bitterlich & Schaber, 1986;MacDonald et al, 1986). It has been suggested that intracellular protein digestion is nutritionally important in fish larvae before gastric gland differentiation, and is restricted to the hindgut (Watanabe, 1984;Vernier, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…1.6), εξαρτώνται από τους μικροοργανισμούς που υπάρχουν στο περιβάλλον του ατόμου, τη φυσιολογία του, αλλά και την απόκρισή του στους αρχικούς μικροβιακούς εποικιστές (Wilkinson, 2002). Έχει αποδειχθεί επίσης, ότι παράγοντες όπως η ηλικία, η διατροφή, περιβαλλοντικές συνθήκες, καθώς και γενετικοί παράγοντες του ξενιστή, επηρεάζουν την μικροβιακή ποικιλότητα στο γαστρεντερικό σύστημα των ιχθύων (Sakata et al, 1980;Bitterlich & Schaber, 1986;MacFarlane et al,1986;Kim et al, 2007;Navarrete et al, 2009;Ward et al, 2009;Kormas et al, 2014;Mente et al, 2018). Ωστόσο, θεωρείται ότι η πρώτη εποίκιση του εντέρου μπορεί να επηρεάσει την αυτόχθονη ποικιλότητα του και στα επόμενα στάδια ανάπτυξης του ατόμου (Hansen & Olafsen, 1999).…”
Section: ο ρόλος της γαστρεντερικής μικροβιακής κοινότητας στους ιχθύες και παράγοντες που τη μεταβάλλουνunclassified
“…• ο οικοδίαιτος γρύλλος Acheta domesticus, ο στικτός μαύρος γρύλλος Gryllodes sigillatus και ο αγροδίαιτος γρύλλος Gryllus assimilis 1.4.6. Υποκατάσταση ιχθυαλεύρου και ιχθυελαίου στις ιχθυοτροφές και επιπτώσεις στη μικροβιακή γαστρεντερική κοινότητα των ιχθύων Όπως έχει ήδη αναφερθεί, το γαστρεντερικό μικροβίωμα των ιχθύων φαίνεται να επηρεάζεται σημαντικά από παράγοντες όπως η ηλικία, το περιβάλλον και η διατροφή (Sakata et al, 1980;Bitterlich & Schaber, 1986;MacFarlane et al, 1986;Kim et al, 2007;Navarrete et al, 2009;Ward et al, 2009). Δεδομένου ότι η αντικατάσταση των συμβατικών συστατικών των ιχθυοτροφών φαίνεται δυνατή, η μεταβολή των μικροβιακών κοινοτήτων του γαστρεντερικού συστήματος των ιχθύων σε διατροφικά πειράματα με τα νέα πειραματικά σιτηρέσια προκαλεί ανησυχία.…”
Section: μεταποιημένες ζωικές πρωτεΐνες (μζπ) από μη μηρυκαστικά ζώαunclassified